Guidelines on the diagnosis and management of iron deficiency and anemia in inflammatory bowel diseases. - Gasche, C; Berstad, A; Befrits, R; Beglinger, C; Dignass, A; Erichsen, K; Gomollon, F; Hjortswang, H; Koutroubakis, I; Kulnigg, S; Oldenburg, B; Rampton, D; et al. (2007)
Anemia is a common complication of inflammatory bowel diseases. An international working party has formed and developed guidelines for evaluation and treatment of anemia and iron deficiency that should serve practicing gastroenterologists. Within a total of 16 statements, recommendations are made regarding diagnostic measures to screen for iron- and other anemia-related deficiencies regarding the triggers for medical intervention, treatment goals, and appropriate therapies. Anemia is a common cause of hospitalization, prevents physicians from discharging hospitalized patients, and is one of the most frequent comorbid conditions in patients with inflammatory bowel disease. It therefore needs appropriate attention and specific care.